Miejsce melancholii w kulturze staropolskiej w świetle kazań pogrzebowych przełomu XVII i XVIII w. - Bąk, Justyna (In Gremium. Studies in History, Culture and Politics, 2015)
Place of melancholy in Old Polish culture in the light of the funeral sermons in the turn of 17th and 18th century. Melancholy is a concept of a rich semantic structure. Old Polish concept of melancholy was formed under the influence of ideological currents of the era and served mainly as the expression of thought and reflection on the passing time, in which the phenomenon of death played a key role. In the Middle Ages the term of melancholy, known as acedia at that time, was perceived as a sin. For a man of the Baroque death was the harbinger of eternal life, which is why his attention was firmly focused on eschatological concepts. The matter of the funeral sermons and guidebooks of proper dying were made to persuade a man to a pious life and give him hope for a rebirth in eternity. Especially when he experienced suffering or at the time of his death. Preachers much of their attention devoted to emphasize the important role of hope as the essence of the Christian faith. It supposed to be the remedy for sadness and the melancholic trance for those families which lost their loved ones. Because melancholy led men to second thoughts about God’s creation and led to the loss of health. Melancholy was longing for the passaging time. The indescribable grief over human imperfection and its destructive nature